2017
DOI: 10.1152/ajprenal.00344.2016
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin1 plays a key role in kidney development and renal fibrosis

Abstract: Gremlin1 (Grem1), an antagonist of bone morphogenetic proteins, plays a key role in embryogenesis. A highly specific temporospatial gradient of Grem1 and bone morphogenetic protein signaling is critical to normal lung, kidney, and limb development. Grem1 levels are increased in renal fibrotic conditions, including acute kidney injury, diabetic nephropathy, chronic allograft nephropathy, and immune glomerulonephritis. We demonstrate that a small number of grem1−/− whole body knockout mice on a mixed genetic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 35 publications
(73 reference statements)
4
50
0
Order By: Relevance
“…Although exogenously applied BMP2 has been shown to regulate Gremlin1 expression in developmental models, it had no effect on expression in gingival fibroblasts, suggesting it may be regulated by an alternative BMP or different ligand class. Interestingly, Gremlin1 has also been postulated to have a BMP‐independent role in differentially modulating angiogenesis dependent upon its dimeric state via binding of vascular endothelial growth factor (VEGF) receptor 2 (VEGFR2) and is associated in renal development and upregulated in fibrotic conditions of the kidney, lung and rheumatoid arthritis …”
Section: Discussionmentioning
confidence: 99%
“…Although exogenously applied BMP2 has been shown to regulate Gremlin1 expression in developmental models, it had no effect on expression in gingival fibroblasts, suggesting it may be regulated by an alternative BMP or different ligand class. Interestingly, Gremlin1 has also been postulated to have a BMP‐independent role in differentially modulating angiogenesis dependent upon its dimeric state via binding of vascular endothelial growth factor (VEGF) receptor 2 (VEGFR2) and is associated in renal development and upregulated in fibrotic conditions of the kidney, lung and rheumatoid arthritis …”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated a protective association of variant rs1880646 in NTN1 at 17p13 with NSCL±P in this same case‐control sample (Machado et al, ). As rs1880646 in NTN1 and SNP in GREM1 showed similar protective effects and both genes are associated with apoptotic phenotypes (Broutier et al, ; Church et al, ; Costello et al, ; Michos et al, ), which are essentials for normal embryogenesis, we further performed pairwise SNP‐SNP interaction analysis. Three of the GREM1 SNP (rs16969862, rs16969681, and rs16969816) revealed significant interactions with rs1880646 in NTN1 , with p values of interactions resisted to Bonferroni adjustment for multiple testing and to 1,000 permutation test (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the detection of interactions between SNP within distinct chromosomes, not in linkage disequilibrium, suggests that these interactions are neither sporadic nor the spurious artifacts of genotyping. Previous studies demonstrated that GREM1 and NTN1 are expressed in the craniofacial region during early development of the palate (Leslie et al, ; Ludwig et al, ) and functional analyses suggest that encoded proteins are related to apoptosis (Broutier et al, ; Church et al, ; Costello et al, ; Lahlali et al, ; Michos et al, ). Although genetic association studies often focus on coding SNP, particularly nonsynonymous SNP resulting in amino acid changes because they are likely to be functional, recent studies have showed that SNP in other regions, including in intronic regions as those in GREM1 and NTN1 , may also have regulatory functional consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gremlin-1 can induce angiogenic effects and fibrosis in organs, contributing to progression of cancer development of complex diseases [8]. The overexpression of gremlin-1 in cancer-associated fibroblasts has been reported [35].…”
Section: Discussionmentioning
confidence: 99%